2014
DOI: 10.1177/0165025414551762
|View full text |Cite
|
Sign up to set email alerts
|

The impact of accommodative coping on well-being in childhood and adolescence

Abstract: Coping research has consistently shown that accommodative coping is positively correlated with individuals' health. Until now, however, there have been little to no studies on the prognostic impact of accommodative coping on health, and only a few studies investigating its buffering effect on the relation between stress and health in childhood and adolescence. Thus, two main research questions were tracked in two longitudinal studies: Study 1 investigated if accommodative coping is indeed a functional resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 76 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…Cronbach's alpha increased up to .67 for TGP and .71 for FGA. Negative‐part whole correlations and lower internal consistencies (around α = .70) in younger samples is known from other studies (Greve & Thomsen, ; Thomsen & Greve, ; Thomsen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Cronbach's alpha increased up to .67 for TGP and .71 for FGA. Negative‐part whole correlations and lower internal consistencies (around α = .70) in younger samples is known from other studies (Greve & Thomsen, ; Thomsen & Greve, ; Thomsen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Thus, individuals are able to adapt their goals flexibly by means of two processes: goal engagement (GE) and goal disengagement (GD). Cross-sectional and longitudinal research on the functionality of both goal adjustment processes has consistently shown that their flexible use leads to better physical health and psychological well-being in childhood and adolescence (Band & Weisz, 1990;DeCarlo Santiago & Wadsworth, 2008;Thomsen, Fritz, M€ oßle, & Greve, 2015) as well as in adulthood (Brandtst€ adter, Wentura, & Greve, 1993;Wrosch, Miller, Scheier, & de Pontet, 2007;Wrosch & Sabiston, 2012;Wrosch, Scheier, Miller, Schulz, & Carver, 2003). Cross-sectional and longitudinal research on the functionality of both goal adjustment processes has consistently shown that their flexible use leads to better physical health and psychological well-being in childhood and adolescence (Band & Weisz, 1990;DeCarlo Santiago & Wadsworth, 2008;Thomsen, Fritz, M€ oßle, & Greve, 2015) as well as in adulthood (Brandtst€ adter, Wentura, & Greve, 1993;Wrosch, Miller, Scheier, & de Pontet, 2007;Wrosch & Sabiston, 2012;Wrosch, Scheier, Miller, Schulz, & Carver, 2003).…”
Section: What Does This Study Add?mentioning
confidence: 96%
See 1 more Smart Citation
“…A number of studies have shown that individuals vary considerably with respect to their preparedness and ability to accommodate their goals or values (for an overview see for example Brandtstädter 2006Brandtstädter , 2015Brandtstädter and Rothermund 2002;Schulz 2010, 2019;Haase, Heckhausen, and Wrosch 2013). Accordingly, the individual's FGA (Brandtstädter and Renner 1990) is a predictor for the stability of the self and well-being (Brandtstädter and Greve 1994), and a buffer against aversive circumstances and experiences both for adolescents (Thomsen et al 2015) and adults (e.g. Greve, Leipold, and Kappes 2017; Rühs, Greve, and Kappes 2017).…”
Section: Flexibility Of Goal Adjustment As a Possible Beneficiary Of Multilingualismmentioning
confidence: 99%
“…It is required at the latest when assimilative efforts fail, problems cannot be overcome by active problem solving, or this would involve too much difficulty or cost. A large body of work has shown that the individual capability and tendency for accommodative regulation helps to reduce strain across different kinds of threats and burdens and across different age groups (e.g., Thomsen et al, 2015;Greve et al, 2017;Rühs et al, 2017;for review, Brandtstädter and Rothermund, 2002). Although this has not been a central focus of research, some results suggest that humor might be associated with accommodative coping.…”
Section: Flexibility Of Goal Adjustment As a Perspective-changing Coping Resourcementioning
confidence: 99%